RELIGIUSITAS REMAJA SEKOLAH DITINJAU DARI KOMUNIKASI INTERPERSONAL DALAM KELUARGA DAN PENDIDIKAN AGAMA ISLAM - Al Bone, Abd. Azis (Badan Litbang dan Diklat Kementerian Agama RI, 2005)
Young generation is the hope of the nation to bring this country to a better condition. But if they do not adopt a selective attitude, they will certainly fall into the pit of moral decadence. Reinstating religious and moral values and national identity are things very important to do to avoid the negative impact of globalization. To preserve high morality we need to improve religious education. Good and effective religious education will improve the outputs and, at the same time, the students' religiosity. Besides the efforts done in formal schools, the role of the parents in the family is the other variable that has a significant correlation with the students' religiosity. Both variables are then the stepping point for initiating a discussion.